Emerging Practices in Intergovernmental Functional Assignment - Ferrazzi, Gabriele (Routledge Studies in Federalism and Decentralization, 2017)
Attaining the benefits of (especially fiscal) decentralization in government remains an enduring challenge, in part because the re-arrangement of public functions across levels of government has often been carried out poorly. This book aims to provide a firmer conceptual basis for the re-arrangement of public functions across levels of government. In doing so, it offers practical advice for policy makers from developing and emerging countries and development cooperation practitioners engaged in such activity. Combining a theoretical approach for inter-governmental functional assignment with an in-depth analysis of real-life country cases where functional assignment (FA) has been supported in the context of international development cooperation, it underscores the common technical and political challenges of FA, and also demonstrates the need to expect and support country made and context-specific solutions to FA processes and results. Examples are drawn from a number of developing/transition countries from the Asia-Pacific region, Africa and the OECD, which outline and suggest advisory approaches, tools, principles and good practices and approaches. This text will be of key interest to scholars, students, policy-makers and practitioners in public policy, decentralization, local governance studies, public administration and development administration/studies. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.